Effect of replacement different levels of sesame meal as a protein source to replace soybean meal on the productive performance and reproductive of laying quail - Younis, Duraid Thonnon; Al-Sofee, Khalid Hadi Mustafa (Journal of agricultural, environmental and veterinary sciences, 2021)
The study was conducted in the poultry field in the Animal Production Department/ College of Agriculture and Forestry/ University of Mosul, for the period from 18/ 2/ 2020 until 13/ 4/ 2020. The experiment aimed to study the effect of replacement different levels of sesame meal (SSM) as a protein source to replace soybean meal (SBM) on the productive performance and reproductive of laying quail, 360 quail birds (240 females and 120 males) were used, at the age of 49 days, distributed randomly into five treatments, each treatment with eight replicates, ( 9 birds in each replicate 6 females and 3 males). The treatments were as follows: the first was the control (0% SSM), the second, third, fourth, and the fifth replaced SSM by SBM with level (25, 50, 75 and 100%) respectively, feed and water was ad libitum during the trial period of 8 weeks. The results of the statistical analysis showed there is a significant statistical difference at a level (P≤0.05) in the fifth treatment (100% SSM) as compared to control and other treatments in total egg number, average egg weight, total egg mass, Hen day egg production percentage (% HD), feed intake, feed conversion ratio, fertility, and hatching percentage of total eggs, average weight of hatched chicks, and a significant increase in the embryo mortality. The results also showed a significant decrease at a level (P≤0.05) in the feed intake for the fourth treatment (75% SSM) compared to the control, while no significant differences were observed for the other treatments in all the studied traits. The results of this study showed the possibility of using sesame meal as a protein source at (75%) to replace soybean meal in laying quail bird diets.
Keywords: quail bird; sesame meal; production performance; reproductive performance